Stress-induced structural changes in La-doped BiFeO3-PbTiO3 high-temperature piezoceramics - Leist, Thorsten; Webber, Kyle Grant; Jo, Wook; Aulbach, Emil; Roedel, Juergen; Prewitt, Anderson D.; Jones, Jacob L.; Schmidlin, Josh; Hubbard, Camden R. (Acta Materialia, 2010)
High-temperature piezoelectric polycrystalline ceramics of the system (1 - x)(Bi1-yLay)FeO3-xPbTiO(3) (BF-PT), which are mixed phase in their consolidated state, have been investigated by in situ neutron diffraction during the application of uniaxial compressive stress. It is suggested that the achievable strain in BF-PT is largely generated by straining of the rhombohedral phase. The results of the neutron diffraction measurements are compared and discussed with respect to the measured macroscopic ferroelastic constitutive behavior for various compositions of BF-PT. (C) 2010 Acta Materialia Inc. Published by Elsevier Ltd All rights reserved.
Keywords: Piezoelectricity; Ferroelectncity; Neutron diffraction